2021
DOI: 10.1111/ger.12528
|View full text |Cite
|
Sign up to set email alerts
|

Care partner–assisted intervention to improve oral health for older adults with cognitive impairment: A feasibility study

Abstract: Poor oral health has a significant effect on the overall health and well-being of older adults, and negatively influences functional ability, diet and nutrition. 1,2 Despite the fact that poor oral health is common among older adults, it is often an overlooked area of healthy aging. 3,4 Poor oral health is increasingly linked to adverse health outcomes, including chronic pain, aspiration pneumonia, diabetes and cardiovascular disease. 5 Poor oral health is especially pronounced among cognitively impaired older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Good oral hygiene practice (eg, brushing and flossing) can effectively remove plaque and decrease gingival inflammation. 16 , 17 Maintaining good oral hygiene is critical for preventing periodontal disease. The current study aimed to assess direct and indirect relationships between having both poor oral health and DM and CRP levels as well as test the mediating effect of oral hygiene practice (i.e., flossing) on the relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Good oral hygiene practice (eg, brushing and flossing) can effectively remove plaque and decrease gingival inflammation. 16 , 17 Maintaining good oral hygiene is critical for preventing periodontal disease. The current study aimed to assess direct and indirect relationships between having both poor oral health and DM and CRP levels as well as test the mediating effect of oral hygiene practice (i.e., flossing) on the relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al also showed that dental plaque levels and gingival inflammation were reduced. They furthermore demonstrated good feasibility of an informal caregiver‐assisted intervention on daily oral hygiene care 20 …”
Section: Resultsmentioning
confidence: 99%
“…The studies have been conducted in Europe, the United States and the United Kingdom. The four cohort studies described a telephone help line on oral health and dementia, 17 a mobile geriatric dental programme in adult day health centres, 18 the effect of a preventive oral health care intervention 19 and the feasibility of an informal caregivers‐assisted intervention to improve the oral hygiene of community‐dwelling older people with a cognitive impairment 20 . The studies assessed a representative selection of the population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations